Legal Reform and Strengthening of The Financial Services Authority (OJK): Protecting Investors From Insider Trading in Indonesia - Syazali, Emir Adzan; Najwan, Johni; Muskibah, Muskibah (As-Siyasi: Journal of Constitutional Law, 2024)
This study aims to analyze and critique the legal protections for investors against insider trading practices in Indonesia’s capital market, while highlighting the importance of strengthening the Financial Services Authority (OJK) in ensuring legal justice for investors. Utilizing a normative juridical method, this study employs various approaches, including the statute approach and the conceptual approach. The findings of this study reveal that the regulation of protection against insider trading in Indonesia's capital market remains inadequate due to legal gaps in the Capital Market Law, which has not comprehensively addressed issues, particularly regarding secondary tippees. Thus, a revision of the Capital Market Law is necessary to address these legal gaps by adopting the theory of abuse and regulating secondary tippees. Consistent and strict law enforcement must be enhanced. Furthermore, strengthening the capacity of the OJK is essential, including the use of technologies such as big data analysis and artificial intelligence to detect transaction anomalies more effectively. In addition to strengthening the internal capabilities of the institution, cooperation with other parties, such as law enforcement agencies and international bodies, is also crucial